Comparison of surgical success between two different approaches of the lacrimal pathway, External and Transcanalicular Dacryocistorinostomy, and between two different age groups. - Joana Raquel Costa; Maria Casanova; Teresa Soares; Cecília Almeida e Sousa (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Objective: Compare the surgical success rate of dacryocystorhinostomy (DCR) between (1) two different techniques: External-DCR vs Transcanalicular-DCR; and comparing (2) two different age groups: <65 years vs ≥65 years.